Impact of radiotherapy on psychological, financial, and sexual aspects in postmastectomy carcinoma breast patients: A prospective study and management - Neelam Sharma; Abhishek Purkayastha (Elsevier, 2017)
Objective: The aim of this study was to assess the impact of radiotherapy (RT) on psychological, financial, and sexual aspects in postmastectomy carcinoma breast patients affecting their quality of life (QOL) before, during, and after RT with a strong emphasis on their management and rehabilitation aspects. Methods: A cross-sectional study carried out in a specialized institution, comprising sixty women. Two standardized questionnaires European Organization for Research and Treatment of Cancer (EORTC) 30-item Quality of Life Questionnaire and Quality of Life Questionnaire breast cancer-23 (QLQ-BR23) for health-related quality, translated and validated for the Hindi language were used. The scores' manual of the EORTC was used to calculate the domain scores of the questionnaires. Results: According to the first questionnaire, the emotional function was most affected even at onset of RT treatment and it was worst at the completion of RT treatment with a mean score of 63.75. The global QOL score was also worst at the end of radiation treatment with a mean score of 32.36, while the score 3 months after completion of treatment was 68.16. The symptoms with the highest scores were insomnia with a worst scoring at completion of treatment (29.99), fatigue (26.57), and pain (23.05). According to the QLQ-BR23, the mean score for side effects such as sexual functioning was minimum 0.55 at the completion of RT, which improved to 11.66 on the first follow-up after 3 months. Mean future perspective score which was 57.22 before the start of RT which was reduced to 50.55 at completion, which means that many women experience side effects of RT and impaired sexual satisfaction. Conclusions: Women with breast cancer showed changes in the following domains: financial, emotional, sexual satisfaction, and future prospects. The most frequently mentioned symptoms were fatigue, insomnia, and pain.